SCHOOL FINANCIAL MANAGEMENT: EFFECTIVE STRATEGIES TO INCREASE EFFICIENCY AND TRANSPARENCY - Vincent Nuari (Adisam Publisher, 2025)
School financial management plays a crucial role in achieving operational efficiency and success of educational institutions. In this context, this study examines various financial management strategies that can increase efficiency and transparency in schools. Research focuses on implementing a transparent financial system, adopting the latest information technology such as financial software and ERP systems, as well as developing policies that support accountability and clear reporting. The analysis shows that by integrating technology into financial management practices, schools can gain the ability to manage resources more effectively, conduct more accurate monitoring and evaluation, and increase transparency in the use of funds. In addition, continuous training for financial staff and the implementation of regular external audits play an important role in ensuring the implementation of good governance principles and compliance with established financial standards. Implementing good and modern financial management strategies not only increases efficiency and transparency, but also strengthens public trust in the education system. It is recommended that educational institutions be more proactive in adopting innovations in financial management to maximize the use of resources and support the achievement of broader educational goals.